Blatant domination and subtle exclusion: The mediation of moral inclusion on the relationship between social dominance orientation and prejudice. (January 2016) - Passini, Stefano; Morselli, Davide
Abstract: In this research, we focus on the effects of the individual's social dominance orientation (SDO) on the expression of prejudicial attitudes. Furthermore, we examine the mediational effect of moral exclusion on this relationship. The literature has shown a strong correlation between SDO and prejudice. However, we hypothesize that the processes of moral exclusion (i.e., covert and institutionalized forms of excluding social groups from the community to which the rules of justice apply) should mediate the effect of SDO on the expression of prejudice, particularly with regard to subtle forms of prejudice. The results from 276 Italian participants support this hypothesis. The effects of SDO are mediated by the inclusive level of the moral community, and this effect is stronger for subtle prejudice than for blatant prejudice. The results suggest that modern prejudice is hidden by subtle forms of moral exclusion. Graphical abstract: Highlights: We analyze the mediation of moral inclusion on the SDO/prejudice relationship. Moral inclusion processes involve the extension of social justice to outgroups. 276 Italian subjects served as participants. Moral inclusion mediation was full for subtle and partial for blatant prejudice.